Silicon on C:N:P stoequiometry and nutritional efficiency of sugarcane grown under water deficit in three tropical soils - Costa, Milton Garcia [UNESP] (2023)
The benefit of silicon (Si) in the lives of the plants is undeniable, mainly the physiological and biochemical benefits, mainly in sugarcane plants in conditions of water deficit. However, little was understood about the impact of this beneficial element on modifying the homeostatic balance of carbon (C) – nitrogen (N) – phosphorus (P) and on the nutritional efficiency of sugarcane plants and whether these changes are enough to alter crop dry mass production under different soil conditions in the tropics. In order to broaden the understanding of the benefit of Si, the present study was carried out, aiming to evaluate the supply of Si, via fertirrigation, is sufficient to modify the homeostatic balance of C:N:P and increase the nutritional efficiency of sugarcane plants under water deficit in three tropical soils. For this, three experiments were carried out with pre-sprouted seedlings of sugarcane in three tropical soils (Dystrophic Red Latosol, Eutrophic Red Latosol and Quartzarenic) under controlled conditions in a greenhouse in two cycles of 150 days (1st cycle and 2nd cycle). Silicon was supplied via fertigation at a concentration of 1.8 mM every two days using the stabilized sodium silicate source with sorbitol. Biological losses caused by water deficit in sugarcane plants are related to the homeostatic imbalance of C:N:P, causing reductions in nutrient use efficiency and directly impacting dry mass biosynthesis. Silicon becomes a viable agronomic alternative in sugarcane crops with water restriction, reducing biological losses due to water deficit, modifying the homeostatic balance of C:N:P, improving the efficiency of use of these nutrients and improving the plant performance. The use of Si in sugarcane cultivation without stress was also efficient in improving plant performance, alternating the homeostatic nutritional balance, increasing the efficiency of use of C, N and P and increasing the production of dry mass of leaves and stems. The responses of sugarcane plants to Si application are limited depending on the type of cultivation soil, altering the intensity of responses to the benefits of the beneficial element. The strategic use of fertigation with Si in a water deficit regime becomes more advantageous in tropical soils with low availability of Si in the soil solution, such as the Quartzarenic Neosol. The perspective of the research is that Si can contribute to the sustainable cultivation of sugarcane in tropical soils in irrigated regions or under a regime of water deficit.